Огляд сучасних розумних паркувальних підсистем в системах Smart Home - Гнатченко, Є. В. (ХНУРЕ, 2025)
The overview of various ways of implementing the integration of parking subsystems into the «Smart Home» system, which will ensure the possibility of safe parking maneuvers in a limited space. A comparison of the effectiveness of implementations in different configurations in the smart home system is considered. The study also analyzes the role of IoT technologies in optimizing parking management, enhancing security, and ensuring energy efficiency. Special attention is paid to the impact of edge computing and real-time data processing on reducing delays in parking automation.
Keywords: розумна система; паркувальна система; технологія Smart